Warisan Budaya Aceh: Tradisi, Seni, dan Identitas Lokal - Ratna Dewi; Dinda Amara Putri; Fauziyah Fauziyah; Siti Nurelisah; Vira Dwi Amaliah (Lembaga Pengembangan Kinerja Dosen, 2025)
Aceh is known as a province with cultural diversity and customs that are the outlook on life of its people. Customs are highly preserved because they are ancestral heritage that must be passed on to the next generation. One important aspect of culture is the regional language, which is an inseparable part of people's lives. Language functions as a means of communication to interact and build social relationships. Language is a meaningful expression used to convey messages that can be understood by the listener (Rizky, 2012). The Acehnese people are known to have a strong culture, reflected in the expression